Eucalyptus torelliana as a Raw Material for Paper Pulp - Guha, S. R. D.; Singh, Man Mohan; Sabharwal, H. S. (Indian Forester, 1970)
Eucalyptus torelliana is one of the potential species of Eucalyptus suitable for being introduced in India for production of paper pulp. Results of laboratory scale studies on this raw material indicate that it is a promising raw material for production of sulphate pulp for wrapping papers and of bleached pulp for writing and printing papers.